2022
DOI: 10.1038/s41598-022-05095-0
|View full text |Cite
|
Sign up to set email alerts
|

Twenty seconds of visual behaviour on social media gives insight into personality

Abstract: Eye tracking allows the researcher to capture individual differences in the expression of visual exploration behaviour, which in certain contexts has been found to reflect aspects of the user’s preferences and personality. In a novel approach, we recorded the eye movements of 180 participants whilst they browsed their Facebook News Feed and employed a machine learning approach to predict each of the self-reported Big Five personality traits from this viewing behaviour. We identify that specific visual behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This differences may have led to differences in social cues processing and social strategies that were previously shown to be closely linked to personality (28). This might explain why Openness, Neuroticism and Agreeableness were successfully predicted 5-8 times in the current study and in the experiments with recommendation interfaces (38), while they did not arise in the experiment with social network browsing task, with no direct interactions with other people (39).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…This differences may have led to differences in social cues processing and social strategies that were previously shown to be closely linked to personality (28). This might explain why Openness, Neuroticism and Agreeableness were successfully predicted 5-8 times in the current study and in the experiments with recommendation interfaces (38), while they did not arise in the experiment with social network browsing task, with no direct interactions with other people (39).…”
Section: Discussionmentioning
confidence: 59%
“…assessment element at the end). Laboratory studies showed prediction accuracy of .40 -.70 for Conscientiousness using such tasks as information seeking (19), social network browsing (39) and decision making (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They revealed that the visual behaviour of individuals engaged in an everyday task can predict four of the Big Five personality traits (neuroticism, extraversion, agreeableness, and conscientiousness) as well as perceptual curiosity. Building on Hoppe’s work, Woods et al, ( 57 ) demonstrated that using just twenty seconds of visual behaviour on social-media gives insight into personality traits.…”
Section: Introductionmentioning
confidence: 99%